Sustainable Corporate Governance and Reporting Quality: Evidence from Developing Economy - Khan, Muhammad Yar (European Journal of Sustainable Development, 2025)
This study investigates the relationship between sustainable corporate governance practices and financial reporting quality. Using?a sample of non-financial firms listed on the Pakistan Stock Exchange from 2014-2024, the study adopts panel logistic regression random effect model as baseline analysis. The current study finds a significant negative correlation between sustainable corporate governance score, institutional ownership and board size with the likelihood of financial reporting quality in firms listed in non-financial sector in?Pakistan. The empirical findings also showed a weak effect of independence of the board and family?ownership on the quality of the financial information. To the best of our information,?this is the first ever study to develop a governance score based on the recently introduced code of corporate governance and explore its possible relation with the risk to financial reporting quality in term of manipulations in an Asian emerging market. Based on M-score model, this research adds to the existing literature on sustainable corporate governance and financial reporting quality in emerging economies. Keywords: Sustainable Corporate Governance, Financial Reporting Quality, Corporate Governance Index, Ownership Structure, Board Independence